Henlo fren wuld u do me an educate? : Understanding Doggolingo and readers’ attitudes towards the language - Thng, Vicki Kai Ting (Nanyang Technological University, 2020)
The interconnectivity of the world is now made easy with the internet. Being a platform for the manifestation of meme culture, the internet has resulted in the development of new internet language varieties. One of the newest internet sublanguages is Doggolingo, where images and videos of dogs have embedded captions written in a language punctuated with grammatical variations, spelling transformations, specialised vocabulary and more. This paper introduces Doggolingo and its language rules, draws comparisons with older internet languages such as 4Chan, Leetspeak and LOLSpeak, and compares languages attitudes towards Doggolingo speakers and non-Doggolingo speakers. In order to do so, a Handbook of Doggolingo was created for better understanding of the corpus. The Handbook of Doggolingo was created by collecting Doggolingo utterances found on Instagram posts by the account, @doggosbeingdoggos, one of the first social media pages dedicated to the language. Next, a survey was sent out to 50 participants, and compiled results were statistically interpreted to explore the attitudes towards Doggolingo speakers. Additionally, sentiments were also collected regarding expectations and wants for the future of Doggolingo. The findings of this study show that this meme language is only moderately understandable due to participants’ lack of familiarity with its non-standard linguistic features. However, their understanding improves when presented with a pictorial form of the meme. The attitudinal study shows that participants’ opinions about Doggolingo speakers are either neutral or extremely positive.